P33 What do doctors know about the clinical course of recovery from community-acquired pneumonia?. (September 2018) - Sabu Tharakan, C; Lim, WS; Pick, H; Bains, M; Ashton, D
Abstract : Background: Community-acquired pneumonia (CAP) poses a significant clinical and economic burden in the United Kingdom, with an annual incidence rate of 0.5%–1% in adults. The mortality rate upon hospitalisation ranges between 5%–30%. Return to baseline health following CAP can surpass the expected timelines of recovery, with respect to duration and symptom resolution. Little is known about doctors' knowledge in this area. Therefore, this study provides a previously unexplored qualitative insight into doctors' views and knowledge of the clinical course of recovery in patients with CAP, following discharge. Methods: Ten one-to-one semi-structured interviews were conducted with junior doctors, who had experience in managing patients with CAP. Interviews were recorded and transcribed verbatim. Data was analysed using thematic analysis, with a predominantly inductive approach. Results: Whilst doctors maintained consensus on their proficiency in diagnosis and treatment, their knowledge and awareness of clinical recommendations for post-discharge care were less comprehensive and definitive. No patient information resources on the recovery process from CAP were mentioned, even though many believed this would be beneficial. Similarly, doctors highlighted a lack of awareness and/or availability of targeted support services to aid patients with their recovery. Doctors are knowledgeable to varying degrees about the impact of the recovery process on patients. When managing patient's expectations of recovery, it is evident that doctors provide general advice based on their clinical experience, rather than evidence. Many also noted that patients with CAP seek reassurance, often afraid of recurrence upon hospital discharge. Conclusion: Doctors have mixed views on the current management of patients with CAP following discharge. Many concurred that patients experience anxiety and morbidity associated with recovery from CAP. Also, a perceived deficiency in the support infrastructure for affected patients was noted. Thus, further research could consider post-discharge management and recovery, in order to improve existing clinical recommendations and resources.